SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN MEDIA PEMBELAJARAN TERBAIK DI SEKOLAH MENGGUNAKAN METODE SAW DAN TOPSIS - Wijayanto, Wendhie Tri; Kristianto, Taufik Fredy; Ajie, Ach. Ridlo Bayu; Nugroho, Kristiawan; Ardhianto, Eka (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstrack: Digital transformation in education demands the development of a comprehensive decision support system to optimize the selection of learning media in educational institutions. This study aims to develop a multi-criteria evaluation framework using a combination of the Simple Additive Weighting method and the Technique for Order of Preference by Similarity to Ideal Solution to determine the optimal learning media. The research methodology uses a comparative quantitative approach with a systematic documentation study of eight types of learning media at SMK Bhakti Persada, Kendal Regency during the period of June 2025. The analysis was carried out based on four main criteria: learning effectiveness, interactivity, ease of use, implementation costs. The results showed that digital technology-based learning media dominated with 62.5%, where e-learning platforms achieved the highest ranking in SAW (1,000) and optimal interactive multimedia in TOPSIS (0.699). The Spearman correlation coefficient of 0.976 confirmed methodological consistency with expert judgment validation reaching an acceptance level of 89.2%. The developed system makes a significant contribution to optimizing the allocation of educational resources through objective and measurable evidence-based decision making.Keyword: decision support systems, learning media, multi-criteria evaluation. Abstrak: Transformasi digital dalam dunia pendidikan menuntut pengembangan sistem pendukung keputusan yang komprehensif untuk optimalisasi pemilihan media pembelajaran di institusi pendidikan. Penelitian ini bertujuan mengembangkan framework evaluasi multi-kriteria menggunakan kombinasi metode Simple Additive Weighting dan Technique for Order of Preference by Similarity to Ideal Solution untuk menentukan media pembelajaran optimal. Metodologi penelitian menggunakan pendekatan kuantitatif komparatif dengan studi dokumentasi sistematis terhadap delapan jenis media pembelajaran di SMK Bhakti Persada Kabupaten Kendal selama periode bulan Juni 2025. Analisis dilakukan berdasarkan empat kriteria utama: efektivitas pembelajaran, interaktivitas, kemudahan penggunaan, biaya implementas.. Hasil penelitian menunjukkan bahwa media pembelajaran berbasis teknologi digital mendominasi dengan 62,5%, dimana platform e-learning mencapai ranking tertinggi dalam SAW (1,000) dan multimedia interaktif optimal dalam TOPSIS (0,699). Koefisien korelasi Spearman sebesar 0,976 mengkonfirmasi konsistensi metodologis dengan validasi expert judgment mencapai tingkat penerimaan 89,2%. Sistem yang dikembangkan memberikan kontribusi signifikan terhadap optimalisasi alokasi sumber daya pendidikan melalui pengambilan keputusan berbasis evidence yang objektif dan terukur. Kata-kata Kunci: sistem pendukung keputusan, media pembelajaran, multi-kriteria evaluasi.